Sensitivity and specificity of S2BI for identifying alcohol and cannabis use disorders among adolescents presenting for primary care. Issue 3 (3rd July 2021) - Levy, Sharon; Weitzman, Elissa R.; Marin, Alexandra C.; Magane, Kara M.; Wisk, Lauren E.; Shrier, Lydia A.
Abstract: Background: The Screening to Brief Intervention (S2BI) tool was designed to identify substance use disorders in adolescents. We report the S2BI's sensitivity and specificity for identifying alcohol and cannabis use disorders (AUD and CUD) in adolescents presenting for primary care. Methods: Participants aged 14–18 ( N  = 517) completed an electronic survey, consisting of the S2BI, the Composite International Diagnostic Interview (CIDI), and anxiety and depression screens. We calculated sensitivity, specificity, and positive and negative predictive value (PPV, NPV) of the S2BI compared to the CIDI criterion standard, using past year "monthly" and "weekly or more" consumption of alcohol or marijuana as a threshold for AUD or CUD. Results: Current AUD and CUD were present in 2.9% and 8.3% of the sample, respectively and severe AUD and CUD were present in 0.8% and 3.9%. The S2BI had 53.3% sensitivity and 94.2% specificity for identifying any AUD (PPV = 21.6%; NPV = 98.5%), and 81.4% sensitivity and 92.0% specificity for identifying any CUD (PPV = 47.9%; NPV = 98.2%). The same threshold had 100% sensitivity and 93.6% specificity for identifying moderate/severe AUD, and 90.0% sensitivity and 89.0% specificity for identifying moderate/severe CUD. Conclusions: S2BI had excellent sensitivity and specificity for identifying moderate and severe AUD and CUD. Sensitivity decreased when mild AUD and CUD were included.